?PEROXYMOLYBDATES PREPARATION, CHARACTERIZATION AND MILD STEEL CORROSION INHIBITION - MUSTAFA, C. M.; BEGUM, D. A.; MOHIUDDIN, M. (Biological Sciences - PJSIR, 1997)
The importance of soluble molybdate compounds as corrosion inhibitor has greatly ’increased due to stringent restrictions on the effluent disposal problem associated with the effective chromate-based corrosion inhibitors. Early reports [1-3] show that molybdate was effective and compa- rable to chromate in the aerated aqueous system. It has been established in recent works [4,5] that molybdate is only effective in the presence of oxygen. It is explained [6] that weak oxidizing property of molybdate is responsible for weak corrosion inhibition in de-aerated media.